Friction and dry sliding wear properties of compact graphite iron at room temperature and 100 °C. (2021) - Venugopal Rao, S.; Venkataramana, M.; Kumar, A.C.S.
Abstract: High brake temperature may cause brake failure of an automobile. To overcome the brake failure it is necessary to determine safe speeds. Brake drum temperature is a variable which depends on speed control and emergency braking. The temperature increase in controlling speed phase of an automobile is less than the emergency braking phase. Cast iron is the material highly used as brake drum due it is high thermal properties. Compacted graphite cast iron (CGI) has applications on account of its superior thermal and wear properties in comparison of grey cast iron. Mainly CGI is useful material in automobile sectors. In automobiles it is used in making of engine blocks, brake drums and exhaust manifolds etc. Brake drums are experienced with high temperatures. In the present study, wear tests were carried out to determine wear behavior and frictional properties which are used to analyze the applications of CGI in making of brake drums. In relation to CGI material applications as brake drums wear tests were conducted at room temperature and at 100 °C. In the present study Dry sliding test is carried out on pin on disc wear testing machine. CGI material worn surfaces are analyzed with SEM analysis. Wear rate and frictional factors of CGI are affected by microstructure behavior and frictional forces between two materials. From the present experimental study it is observed that high wear experienced at starting and then gradually experienced uniform wear developed. Frictional forces also low and uniform at starting and later on little amount of forces increased.